2019
DOI: 10.1155/2019/4592847
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility Analysis of Buildings Based on Double-Parameter Damage Models considering Soil-Structure Interaction

Abstract: Most conventional seismic fragility analyses of RC buildings usually ignore or greatly simplify the soil-structure interaction (SSI), and the maximum interstory drift ratio (MIDR) is often adopted to establish seismic fragility curves. In this work, an eight-story RC building was designed to study the influence of the SSI on the seismic fragility of RC buildings. Three double-parameter damage models (DPDMs) were considered for the fragility assessment: the Park–Ang model, the Niu model, and the Lu–Wang model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As seen in Figures 15 and 16, the maximum inter-story drift, derived from the SSI analysis, appears in the first story. Previous studies also mentioned that the maximum inter-story drift appears in the first floor of the moment-resisting frame buildings constructed on soft soil when the SSI was considered in the analysis [10,[43][44][45]. Also, researchers have indicated that base flexibility results in the large displacement of the first story [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figures 15 and 16, the maximum inter-story drift, derived from the SSI analysis, appears in the first story. Previous studies also mentioned that the maximum inter-story drift appears in the first floor of the moment-resisting frame buildings constructed on soft soil when the SSI was considered in the analysis [10,[43][44][45]. Also, researchers have indicated that base flexibility results in the large displacement of the first story [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…The soil model used in the numerical analysis has dimensions in 3D of 70×20×10 m 3 , where soil is 10 times larger than the structure [31], in order to ensure freefield movement. Soil is represented as a semi-finite domain, which requires the use of dampers at its boundaries to absorb seismic waves and avoid their reflection.…”
Section: Soil Modellingmentioning
confidence: 99%